Rate Control Scheme Based on Cauchy R-D Optimization Model for H.264/AVC under Low Delay Constraint - Eiamjumrus, N.; Aramvith, S. (2006 International Conference on Intelligent Information Hiding and Multimedia Signal Processing : (IIH-MSP 2006) : proceedings ; 18-20 December, 2006, Pasadena, California, USA, 2006)
Base on the observation that Cauchy distribution provides an accurate estimates of rate and distortion characteristics of video sequences. In this paper, we propose to use a new rate control scheme based on Cauchy R-D optimization model for bit allocation of H.264 for low delay constraint. One solution which has been proposed in this paper use the Lagrange Multiplier technique as the cost function to find rate and distortion model subject to target bit rate constraint resulting in optimum of quantization step sizes. Model parameters are estimated using linear regression analysis. We propose a simple rate control scheme that achieves for new Cauchy R-D model in basic unit layer under low delay constraint. The target bits for each frame are determined according to their buffer status, combined with number of bits use in the previous frame. The technique proposed has been implemented on H.264 video coder. Experimental showed that the proposed can be achieves an improvement of average PSNR with smooth video quality and less frame skipping compared to the JM8.6 rate control.